WORK LIFE BALANCE OF ENTREPRENEUR DURING PANDEMIC - Sukanya Kumari; Verma, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Finding a healthy work-life balance was one of the obstacles that the entrepreneur needed to overcome. It is vital for companies as well as the family members of employees that employees be able to successfully balance their personal lives, their professional lives, and their commitments to their families and other loved ones. During the emergency scenario caused by COVID-19, a great number of individuals all over the world were required to labour from a distant location. At first, there were some particular expectations regarding the potential of working from home as a beneficial aspect that will encourage work-life balance. These expectations were detected by some. The passage of time, however, revealed that there were also some bad trends, such as the fact that employees were only ever a phone call or message away from their company, and the fact that uncertainty and spending leisure time with family frequently caused greater stress. As a result of the fact that many businesses and individuals were not prepared for this unexpected transformation, a great number of errors were made, which further brought attention to the problem of maintaining a healthy work-life balance.